2020
DOI: 10.1111/csp2.161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regional economics on the online sale of protected parrots and turtles in China

Abstract: The sale of wild animals, including protected species, may relate to regional differences in socio‐politics, culture, and economic development. A better understanding of how these factors affect the illegal wildlife trade is therefore necessary to optimize the deployment of conservation resources and policing. To evaluate these factors in relation to the trade‐in protected animals as pets, we surveyed China's popular consumer‐to‐consumer website, http://taobao.com (analogous to eBay), and found that over 70,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The scale of the trade and limited knowledge of the direct impact on wild populations justifies reassessing how we regulate international reptile trade. The USA instigated the Lacey Act to prevent animal trafficking in 1900 29 . While the Lacey Act preceded CITES, it expanded to recognise CITES listed species, in addition to species with local regulations on trade and export.…”
Section: Discussionmentioning
confidence: 99%
“…The scale of the trade and limited knowledge of the direct impact on wild populations justifies reassessing how we regulate international reptile trade. The USA instigated the Lacey Act to prevent animal trafficking in 1900 29 . While the Lacey Act preceded CITES, it expanded to recognise CITES listed species, in addition to species with local regulations on trade and export.…”
Section: Discussionmentioning
confidence: 99%
“…of captive breeding,Ye et al (2020) reported that 43 of these 46 nationally and218 internationally protected parrot species (5,798 of the 5,862 individuals) traded on 219 Taobao.com are not native to China, or even to Asia. Of these 46 species, 18 are 220 indigenous to South America, and 14 to Australia and eastern Indonesia.…”
mentioning
confidence: 99%
“…Demand for luxury goods and food is a major driver of global wildlife trade (cited in 35% of 374 reports), followed by traditional medicine (25% of reports) and pets (22%) [ 72 ]. As prosperity increases in China, animal products (ivory, rhino horn, big cat products, etc) [ 73 ], exotic pets [ 41 ] and even animal ingredients in CTM, are perceived as conferring cachet upon their owners [ 2 , 43 ]. The judgement documents we examined did not provide enough information to formally analyze for any relationship between offender socio-demographics and propensity to trade in luxury goods, but, interestingly, women were more highly represented in offences involving rhino horn and elephants/ ivory than in any other type of wildlife crime–often involving artisan or retail work rather than other more physically demanding/ violent wildlife crimes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have dealt extensively with how wildlife crime and trade might be tackled by educating and reforming consumer practices [ 10 ]. In terms of sanction, threats of punishment and incarceration provide a general deterrent against offending [ 23 , 77 , 78 ], weighed against the likelihood of detection and successful prosecution [ 41 ]. In this sense, the per capita rates of prosecution we report seem rather low, and there is other evidence that minor illegal wildlife trading infringements are not always pursued in China; for example, as evidenced by our own work investigating illegal trade in parrots and turtles [ 41 , 79 ] and the illegal sale of protected species through wet markets [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation